FRIEDREICH ATAXIA – A CASE REPORT - V., Deepthi R.; Pavanam, Seema; Shenoy, Vijaya; Joshi, Siddarth S. (Journal of Health and Allied Sciences NU, 2014)
Friedreich ataxia is an autosomal recessive disorder, due to expansion of trinucleotide repeat in Frataxin gene which presents with ataxic gait, absent tendon reflexes, extensor plantar response and positive Romberg test. We present a child who came with complaints of progressive ataxia of gait since the age of 10 years and was diagnosed to have Friedreich ataxia. They have associated cardiomyopathy and endocrine abnormality like diabetes and hypothyroidism.
Keywords: Areflexia; Friedreich ataxia; Extensor plantar response; Romberg's sign; Trinucleotide repeat